Prospects for solar energy in Ukraine in the context of environmentally sound development of the state - Білявський, Г.О.; Титенок, І.В. (Proceedings of National Aviation University (archive), 2009)
General concepts about Sun energy, advantages of sun elements, prospectives of sun energy development in Ukraine are discussed. The best technologies for sun elements production and their application in Ukraine and abroad are considered.